Integrasi Penilaian Psikomotorik dalam Program BK untuk Pengembangan Potensi Siswa - Berlian Cahyani; Mutia Najwa Khairunnisa; Oktavia Utami Ramadhani; Okti Pravitasari; Minarsih Minarsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to (1) identify various models and techniques of psychomotor assessment in learning, (2) analyze assessment instruments that have been developed in various contexts of education, and (3) formulating recommendations for implementing psychomotor evaluations that are relevant to the Guidance and Counseling Services (BK). The method used is a literature study by examining 26 journals published in 2013-2025. The results showed that psychomotor assessment instruments have been widely developed through peer assessment, project based learning, practice demonstrations, rubrics, portfolios, and authentic assessments. These instruments are generally valid, reliable, practical, and effective in measuring the psychomotor skills of students. However, assessments in schools are still dominant in cognitive aspects, so that psychomotor aspects receive less attention. Therefore, this article recommends the integration of psychomotor assessment more balanced with the cognitive and affective domain, both in learning and BK services, so that students not only develop intellectually and emotionally, but also have real skills that are applicable in daily life and the world of work.